Perbedaan Jumlah Porphyromonas endodontalis pada Diagnosis Pulpitis Ireversibel dan Nekrosis Pulpa (Penelitian) - Taufiq Ariwibowo; Bryan Wangidjaja; Meiny Faudah Amin (Fakultas Kedokteran Gigi Universitas Trisakti, 2019)
Background: Pulp diseases can be affected by bacterial invasion such as Porphyromonas endodontalis. This bacterial invasion can lead to pulp diseases which include irreversible pulpitis and necrotic pulp. Purpose: To determine Porphyromonas endodontalis difference between teeth with irreversible pulpitis and necrotic pulp. Method: Samples were taken from root canals fluid of 18 teeth, 9 teeth with irreversible pulpitis, 9 teeth with necrotic pulp, using paper point. The paper point was placed in sterile Eppendorf tube, then DNA were extracted using Heat-Shock DNA Extraction method. Real-time PCR was used to collect the data. The conversion of microbiological data were used standard curve of Porphyromonas endodontalis. Result: The average of Real-time PCR on irreversible pulpitis was 6.9 x 10-12 ng/mL and on necrotic pulp was 1.3 x 10-12 ng/mL. However, t independent test showed there was no significant difference of Porphyromonas endodontalis between teeth with irreversible pulpitis and necrotic pulp (p>0,05) Conclusion: There was no difference in the total number of Porphyromonas endodontalis between teeth with irreversible pulpitis and necrotic pulp.